Batman : the return of Bruce Wayne - Morrison, Grant; Kane, Bob.; Sprouse, Chris (New York : DC Comics, 2011)
Long gone from Gotham and believed dead by most, Bruce Wayne, aka Batman, is lost in time and unaware of who he is and what has happened to him. As Superman and the Justice League search for him, Bruce Wayne jumps through time, living as a caveman, a witch hunter, a pirate, and more, on his way to becoming himself once again.
"Batman created by Bob Kane."
"Originally published as Batman : The Return of Bruce Wayne 1-6"--T.p. verso.
Young Adult.
Young Adult
Keywords: Batman (Fictitious character) -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Space and time -- Comic books, strips, etc -- Fiction; Superheroes -- Comic books, strips, etc -- Fiction; Batman (Fictional character) -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Science fiction graphic novels; Space and time -- Comic books, strips, etc -- Fiction; Superhero graphic novels; Superheroes -- Comic books, strips, etc -- Fiction; Graphic novels; Science fiction comic books, strips, etc; Superhero comic books, strips, etc